Structural health monitoring by Fiber Optic Polarimetric sensors (FOPS) and Fiber Bragg Grating (FBG) - Maheshwari, Muneesh (2016)
Structural health monitoring (SHM) techniques using smart materials are on the rise to meet the ever ending demand due to increased construction and manufacturing activities worldwide. The civil-structural components such as slabs, beams and columns and aero-components such as wings are constantly subjected to some or the other forms of external loading. SHM is one of the most important issues as it prevents overloading, serious damages, also averts risks. A number of methods utilizing different concepts and techniques have already been proposed, but online structural health monitoring is very difficult and ineffective with classical method. The Fiber Optic Sensor (FOS) technologies facilitate real time non-destructive health monitoring of different mechanical and civil structures. These FOS techniques play a very important role in assessing the performance of different engineering structures when they are in operation. The most widely investigated and implemented fiber optic sensors for SHM are Fiber Bragg grating (FBG) and Fiber Optic Polarimetric sensor (FOPS). If the light from a broadband source is launched into the FBG, a very sharp wavelength peak (FWHM ≈ 0.1-0.2 nm) will be reflected back by the FBG or in other words an FBG works as a wavelength filter. This reflected peak shifts if strain, temperature, pressure etc. changes in the FBG. The measurement done by the FBG is very accurate, but it can be used for point measurement only. Thus FBG can monitor local region of the structure. Moreover, the interrogation system of FBG is too bulky and expensive to be used for field applications. In FOPS, polarization maintaining (PM) fiber or high birefringent fiber (Hi-Bi) is used as a sensor. The polarization or the phase of light coming out of FOPS changes if external load or pressure is applied to FOPS. Since the entire FOPS sensor is sensitive, the external perturbations cause a lot of noise in the output signal. Demodulation of the change in the polarization of the light coming out of FOPS signifies the changes in the entire structure with no knowledge of specific location. Therefore, FOPS provides information for global SHM. Location of loading point or damage in the structure is unknown at best in the previous studies. The objective of this research work is to do a combine local and global SHM to find out the location of damage using minimum instrumentation. FBGs have been used to measure load, pressure, temperature etc. FBG can be designed to measure liquid pressures also as shown in the work. Resin pressure distribution of a curing laminate is a key parameter that controls the strength, stiffness and void nucleation of the cured part. It is vital to monitor and control the resin movement of the curing laminate to optimize its quality with any manufacturing process. In this research work, a device consisting of a fiber Bragg grating (FBG) is designed which is capable of measuring in-situ resin pressure. This device uses the principle of differential pressure in liquids. This stable and reliable sensor is quite useful especially for high temperature and low or zero bleed curing of composite laminates, such as out of autoclave curing. In other words, the SHM of curing composites can be performed using FBG sensors proposed in this work. The Fiber Optic Polarimetric Sensor (FOPS) is nothing but a polarization maintaining (PM) fiber which is capable of monitoring damage in structures at global level. However the system is not capable of identifying damage location and crack size, which would further assist in the assessment of the severity of damage. Also, the output signal from FOPS is very noisy because of the fact that the whole fiber is sensitive and picks up unwanted signals from its surroundings. In this research work, a new design of FOPS has been put forward. The output of this design is very stable as only a specific part of FOPS is sensitive. This reduces noise and only the part being monitored can be independently assessed. Theoretical validation of this design is presented. This design is then implemented to locate and estimate the size of a crack in a cantilever thus providing local SHM as well. Damage investigation in a fixed-fixed beam has also been done using this FOPS design. Further, in this research work, it is shown that an FBG written on the Polarization Maintaining (PM) fiber can be used for both global and local SHM simultaneously. Thus, local and global information both are obtained from a single fiber. This reduces costs and complexities. Two PM-FBGs have been multiplexed in a certain way to form a new design of sensor which gives improved information on damaged location in beam structures. Further, by proper multiplexing the PM-FBGs it is possible to predict the damage location in two dimensional structures like, plates too. The damage site in an aluminum plate has been located using this multiplexed sensing array. FBG can monitor the local region surrounding itself using optical spectrum analyzer (OSA), thus providing local SHM only. In this research work, a wavelength shifted chirped FBG (CFBG) interrogation system has been presented. This is an intensity based interrogation system which can measure positive/negative strain and temperature simultaneously. This sensor design abrogates the need for OSA. It also allows the use of simple LEDs as light source. Altogether, this design substantially brings down the cost of interrogation system. This interrogation design is simple and compact with a strain sensitivity of around 5με. Additionally, since this system is intensity based, it can measure the frequencies of fundamental vibrations of any structure which provide the global SHM of the structure. Thus, this system can perform local and global SHM.